Digital transformation of contemporary Ukrainian exhibition and display practices - Tormakhova, Anastasiia; Aleksiienko, Olena (Ukrainian Cultural Studies, 2025)
Background. Over the past decades, digital technologies have transformed artistic practices, expanding the boundaries of artistic expression and exhibition formats by integrating new media, interactive elements, and virtual components into the creative process. This shift is largely driven by technological and societal transformations within contemporary culture. The purpose of the article is to examine the role of digital technologies in the transformation of Ukrainian exhibition and display practices. Methods. To trace how digital technologies have changed exhibition and exposition practices and the ways in which audiences interact with works of art, the study employs a comprehensive approach grounded in cultural analysis. A comparison of traditional and contemporary formats is employed to identify the specific features of immersive art exhibition practices. Additionally, the study adopts a systematic approach, considering immersive technologies not as an isolated phenomenon but as part of a broader digital transformation of culture. Results. Immersive formats engage the viewer as an active participant rather than a passive observer in the artistic process. This creates new opportunities for artistic communication and makes cultural artefacts accessible to a wider audience, regardless of geographical boundaries. Immersiveness also changes the mechanisms of interaction with the art: visual perception becomes supplemented by the complex spatio-physical experience, based on movement and tactile contact. Special role in transforming Ukrainian exhibition practices plays the revitalization of industrial and public architectural spaces, which not only gives new life to abandoned buildings but also creates favourable conditions for large-scale multimedia exhibitions. Conclusions. The study of current transformations in Ukrainian exhibition and display practices demonstrates that the use of new media technologies is reshaping traditional formats. The actualisation of media art, the rise of immersive exhibitions, and the development of VR and AR technologies blur the boundaries between physical and digital spaces and create new ways of interacting with the audience. Immersive technologies have already become an integral part of contemporary art spaces, and their further development creates prospects for expanding the boundaries of artistic expression. At the same time, analyzing this phenomenon–which encompasses not only cultural but also technological, social, and economic dimensions–requires interdisciplinary approaches.